Aspects of Bullying: The Role of Individual Counseling in Emotional Regulation and Social Character Development - Minarsi, Minarsi; Yulianti, Yulianti; Fitriana, Fitriana; Suryani, Yuni Dwi (Jurnal Kajian dan Pengembangan Umat, 2025)
The cases of bullying that arise from romantic relationships among teenagers are becoming more prevalent and have a significant impact on emotional regulation and social character formation. This research aims to analyze the role of individual counseling in helping teenagers manage negative emotions and build positive social character. The method used is a literature study with an analysis of previous research findings and counseling practices in schools. The results show that individual counseling is effective in improving emotional regulation and social skills for both victims and perpetrators of bullying. The discussion emphasizes the importance of school counselors in providing emotion regulation-based interventions and strengthening social character to create a safe and inclusive school environment.